Article Commentary: Dismantling Racism Against Black, Indigenous, and People of Color across the Substance use Continuum: A Position Statement of the Association for Multidisciplinary Education and Research in Substance use and Addiction. Issue 1 (January 2021) - Hagle, Holly N.; Martin, Marlene; Winograd, Rachel; Merlin, Jessica; Finnell, Deborah S.; Bratberg, Jeffrey P.; Gordon, Adam J.; Johnson, Cheyenne; Levy, Sharon; MacLane-Baeder, Doreen; Northup, Rebecca; Weinstein, Zoe; et al.
The Association for Multidisciplinary Education and Research in Substance Use and Addiction (AMERSA) acknowledges that racism profoundly affects persons who use alcohol and other drugs. Racism's deadly effects compounded with other social determinants of health result in a cascade of negative impacts. The AMERSA Board of Directors (BOD) proposes an initial set of strategies to promote diversity, equity, and inclusion using a framework that speaks to four key AMERSA experiences: engagement, education, mentorship, and leadership. Through these strategies, AMERSA commits to promoting equity and inclusion to dismantle the individual, institutional, and structural racism that has permeated the United States for centuries. Abstracts of paper and poster presentations are also provided (Supplemental Material).